Digital Measurement Model as a Support Tool for the Validity of Village Land Administration Data - Sri Wahyu Handayani; Bahar Elfudllatsani; Mohammad Irham Akbar (Universitas Muhammadiyah Purwokerto, 2025)
This research aims to recommend the implementation of the digital measurement model on Village Devices and Land Data Collectors (PULDATAN) so that the collection of land data, both physical and juridical, serves as a means to support the validity of village land data. This aims to support the National Program for Complete Systematic Land Registration as mandated by Article 19 of Law Number 5 of 1960 on the Basic Agrarian Law. The location of this research is conducted in Panembangan Village, Cilongok District, Banyumas Regency. The research on the model of implementing digital measurement in village administration was conducted through the following stages: 1. Updating the Juridical Data of Village Land; 2. Updating the Physical Data of Village Land; 3. Computerization and Digitalization of Village Land Administration. The method used in this research is the empirical juridical method. This research aims to review the application of digital measurement as a form of implementing land administration law in villages to support the validity of land data in the villages. This research produces a digital measurement model in villages to prevent agrarian disputes/conflicts. The validity of village land data is the initial gateway to land administration order.